2012
DOI: 10.2478/v10163-012-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year Overview of Forearm Fracture Etiology and Treatment Options in 7-15 Years Old Children

Abstract: SummaryIntroduction.Forearm fractures make up a significant part of overall fracture rate in pediatric population, especially in 7-15 years old children. Different methods of treatment have been used, depending on the age of children and type and localization of fracture. Most controversies can be seen among conservative and surgical methods of treatment.Aim of the Study.The aim of our study is to identify common localizations and types of forearm bone fractures in pediatric population, as well as analyze pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We could not establish statistically significant correlation, proving that limitations are found more often in younger or older children, but what we found is the difference of treatment efficiency in favor of surgical approach. We have used to consider that surgery is used more for older children, while younger children usually undergo conservative treatment, they have faster healing and thus -better functional outcome [29,33,37]. Our results with patient randomization showed that there are no differences among age groups treated by the same method.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…We could not establish statistically significant correlation, proving that limitations are found more often in younger or older children, but what we found is the difference of treatment efficiency in favor of surgical approach. We have used to consider that surgery is used more for older children, while younger children usually undergo conservative treatment, they have faster healing and thus -better functional outcome [29,33,37]. Our results with patient randomization showed that there are no differences among age groups treated by the same method.…”
Section: Resultsmentioning
confidence: 70%
“…Analyzing influence of the dominating hand, we found that it was injured more often (1.14:1). This is an interesting finding, because usually dominant hand is considered to be "stronger", as it is more used, has increased muscle mass and better tolerance to similar impact (11,33). Despite the wide use of goniometry in physical therapy for objective assessment or ROM, the reliability of using it under clinical settings is variable, and depends significantly on experience of tester and performance of the assessment (intratester errors), number or persons performing the same study (intratester errors), and tool used (intertool errors) (15,17,27).…”
Section: Resultsmentioning
confidence: 99%